PERAN HAK ASASI MANUSIA TERHADAP PERLINDUNGAN PMI YANG MENJADI TAHANAN IMIGRASI DI LUAR NEGERI (Studi Kasus Tewasnya Puluhan WNI di Tahanan Imigrasi Malaysia) - Dinda Ardhya Kusuma Armiyanto (2023)
In the life of every individual, human rights are one of the most important aspects. The rights of every human being have been inherent since he was born, not even the state or anyone who can take away these rights, as the right itself is a gift from God Almighty. Concerning Human Rights itself, it has been regulated in the Universal Declaration of Human Rights in 1948 and has been recognized worldwide. Although the recognition of human rights has been carried out for a long time, violations can still be found today and there are not a few cases. In 2022 there were reports of the deaths of dozens of Indonesian citizens at Malaysian immigration detention centers. Malaysia itself has been bound by several international agreements and does not waive its obligation to ensure the protection of the rights of every human being, including Indonesian migrant workers who have legal problems and are detained in Malaysia. In addition to Malaysia's firmness and consistency in carrying out its obligations, the Indonesian government needs to play a swift and fast role in handling the cases of these Indonesian migrant workers so that unwanted events can be anticipated in the future. The writing method that the writer uses is a normative juridical research method, namely in the form of research on library materials as the main source and uses secondary qualitative data using pre-existing literature such as books, journals, articles, and several related documents.